Size nouns matter: a closer look at mass(es) of and extended uses of SNs. (January 2016) - De Clerck, Bernard; Brems, Lieselotte
Abstract: While a fair share of attention has recently been devoted to the grammaticalization process of size nouns in general (see Traugott, 2008) and individual case studies in particular (see Brems, 2003; Verveckken, 2012; De Clerck & Colleman 2011), there is still enough food for thought and room for further analysis. In this paper we want to address two aspects that have not received sufficient attention so far. First, we will focus on grammaticalized uses of yet two other size nouns (SNs), i.e. mass of and masses of and compare their quantificational potential with other SNs, such as bunch, heap and load of as studied in Brems (2011). This comparison will call for a repositioning of SNs on the grammaticalization cline and a reassessment of the criteria used in Brems (2011) and the notion of degree of grammaticalization. Secondly, we will shift attention away from 'common' quantifying uses to intensifying adverbial uses of SNs, e.g. heaps nicer, and the possible effect these uses have on their current position on the grammaticalization cline.